2021
DOI: 10.3390/jcm10214821
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Acute Encephalopathy in Patients with COVID-19

Abstract: Introduction: The majority of patients with severe COVID-19 suffer from delirium as the main sign of encephalopathy associated with this viral infection. The aim of this study was to identify early markers of the development of this condition. Materials: The prospective cohort-based study included patients with community-acquired pneumonia and confirmed pulmonary tissue infiltration based on CT data, with a lesion consisting of at least 25% of one lung. The main group included patients who have developed acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Consistent with our study, previous analyses have shown that elevated D-dimer and LDH levels are associated with encephalopathy and lung tissue injury, serving as potential early warning indicators for severe neurological changes [12]. Our study also found that IL-6 levels signi cantly increased in patients with severe neurological impairment, consistent with the cytokine storm hypothesis [13], suggesting that using anti-in ammatory therapy to inhibit the cytokine storm may have a certain effect.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our study, previous analyses have shown that elevated D-dimer and LDH levels are associated with encephalopathy and lung tissue injury, serving as potential early warning indicators for severe neurological changes [12]. Our study also found that IL-6 levels signi cantly increased in patients with severe neurological impairment, consistent with the cytokine storm hypothesis [13], suggesting that using anti-in ammatory therapy to inhibit the cytokine storm may have a certain effect.…”
Section: Discussionsupporting
confidence: 91%
“…Aggressive neurological manifestations can predict COVID-19 severity. For example, acute encephalopathy has been linked with severe cases of COVID-19, which was attributed to COVID-19-induced hypoxic brain damage [9]. Another predictor of COVID-19 outcomes was also attributed to the presence of other cardiovascular comorbidities, such as hypertension and diabetes [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The diabetic population also suffers a higher rate of intensive care unit (ICU) admission and mechanical ventilation [7]. SARS-CoV-2 has been shown to cause severe inflammation in various organs, such as the lungs, kidneys, and brain, of diabetic patients [8][9][10][11]. Moreover, Mechi et al reported that diabetic COVID-19 survivors experienced a greater frequency of fatigue and disruptions in concentration and memory, yet the molecular mechanisms are unclear [12].…”
Section: Introductionmentioning
confidence: 99%